2019
DOI: 10.1111/are.13993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary astaxanthin and vitamin E and their interactions on the growth performance, pigmentation, digestive enzyme activity of kuruma shrimp (Marsupenaeus japonicus )

Abstract: A 56‐day feeding trial was done to investigate the interactive effects of astaxanthin (Ax) and vitamin E (α‐Toc) on the performance of kuruma shrimp (Marsupenaeus japonicus). A 2 × 3 factorial experiment was conducted with six experimental diets containing two levels of Ax (0 and 0.6 g/kg diet [Ax0 and Ax0.6]) and three levels of α‐Toc (0, 0.2 and 1 g/kg diet [α‐Toc0, α‐Toc0.2 and α‐Toc1]). The results indicated that growth performance was significantly (p < 0.05) increased in shrimp fed with the Ax0.6 × α‐Toc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…There is a growing interest in the use of functional feed additives as alternative strategy to increase the productivity and for the prevention of diseases in aquaculture (Faggio, Fazio, Marafioti, Arfuso, & Piccione, ; Guardiola et al, ; Hoseinifar, Sun, Wang, & Zhou, ; Hoseinifar, Yousefi, et al, ; Iswarya et al, ; Wang et al, ; Yan, Guo, Dawood, & Gao, ). The application of probiotics in aquaculture has become more prominent across the feed industry due to their growth‐promoting activity (Carbone & Faggio, ; Dawood, Koshio, Abdel‐Daim, & Van Doan, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing interest in the use of functional feed additives as alternative strategy to increase the productivity and for the prevention of diseases in aquaculture (Faggio, Fazio, Marafioti, Arfuso, & Piccione, ; Guardiola et al, ; Hoseinifar, Sun, Wang, & Zhou, ; Hoseinifar, Yousefi, et al, ; Iswarya et al, ; Wang et al, ; Yan, Guo, Dawood, & Gao, ). The application of probiotics in aquaculture has become more prominent across the feed industry due to their growth‐promoting activity (Carbone & Faggio, ; Dawood, Koshio, Abdel‐Daim, & Van Doan, ).…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptome analysis also showed that genes involved in carbohydrate metabolism, lipid metabolism, immune system and endocrine system were significantly enriched in both gill and hepatopancreas, indicating when kuruma shrimp was cultured without sand substrates, its metabolism was critically affected. The digestive enzyme activity plays an important role in nutritional physiology in the crustacean, was directly or indirectly involved in the growth and moulting cycle (Sudtongkong et al., 2019; Wang et al., 2019). Among them, amylase is a well‐known digestive enzyme (Castro et al., 2012; Sakai et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipids play a key role in cells as structural components of membrane lipid bilayers and signalling molecules, implicating its important function in the physiological processes (Aguilera‐Romero et al., 2014). Different from many other animals, shrimp hepatopancreas combines the functions of the pancreas, intestine and liver, playing a vital role in shrimp (Wang et al., 2019). The inhibition of the genes involved in various essential activities is likely responsible for the relatively slow growth of kuruma shrimp cultured without sand substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipase activity was analysed by using olive oil emulsion as the substrate according to Mustafa, Karmali, and Abdelmoez (). Amylase activity was analysed by using starch as the substrate according to Shiu et al () and Wang et al ().…”
Section: Methodsmentioning
confidence: 99%